Activation of peroxymonosulfate by calcined electroplating sludge for ofloxacin degradation. (March 2021) - Peng, Guilong; Qi, Chengdu; Wang, Xiachao; Zhou, Linli; He, Qiang; Zhou, Wei; Chen, Lin
Abstract: Developing cost–effective metal/metal oxides for peroxymonosulfate (PMS) activation remains a key issue in the sulfate radical based advanced oxidation process. In this work, electroplating sludge (ES), a transition metal–rich byproduct, was anaerobic calcined and characterized. Then, calcined electroplating sludge (CES) was applied as PMS activator for degradation of ofloxacin (OFL) and CES/PMS system exhibited a nearly 90% of OFL removal in 60 min. In addition, effect of CES, PMS, the initial pH and water constituents (chloride, bicarbonate, natural organic matter (NOM) and water backgrounds) on OFL degradation were systematically studied. Moreover, radical quenching tests and electron spin–resonance spectroscopy studies manifested that both SO4 – and HO were the ruling reactive oxygen species. X–ray photoelectron spectroscopy results of the fresh and used CES demonstrated that the PMS activation mainly occur in the transformation from Fe 3+ (Cu 2+ ) to Fe 2+ (Cu + ). Furthermore, liquid chromatography coupled with ion trap time–of–flight mass spectrometry was used to illustrate the possible degradation pathway of OFL. Moreover, CES showed excellent stability and reusability during reaction. This work points out a new way for value–added reuse for ES as a cost–efficient activator of PMS for organic contaminant removal. Graphical abstract: Image 1 Highlights: The calcined electroplating sludge can activate peroxymonosulfate efficiently. SO4 – and HO were the ruling reactive oxygen species in CES/PMS system. Possible degradation mechanism and pathway of OFL was proposed.